What is appropriate care? An integrative review of emerging themes in the literature - Joelle Robertson-Preidler; Nikola Biller-Andorno; Tricia J. Johnson (BMC, 2017)
Abstract Background Health care improvement efforts should be aligned in order to make a meaningful impact on health systems. Appropriate care delivery could be a unifying goal to help coordinate efforts to improve health outcomes and ensure system sustainability. A more complete understanding of how appropriate care is currently conceived in research and clinical practice could help inform a more integrated and holistic concept of appropriate care that could guide health care policy and delivery practices. We examined the current understanding of appropriate care by identifying its use and definitions in recently published literature. Methods An integrated review of the practices, goals and perspectives of appropriate care in English language peer-reviewed articles published from 2011 to 2016. Inductive content analysis was used to describe emerging themes of appropriate care in articles meeting inclusion criteria. Results This integrative review included empirical studies, reviews, and commentaries with various health care settings, cultural contexts, and perspectives. Conceptualizations of appropriate care varied, however most descriptions fell into five main categories: evidence-based care, clinical expertise, patient-centeredness, resource use, and equity. These categories were often used in combination, indicating an integrated understanding of appropriate care. Conclusions An understanding of how appropriate care is conceptualized in research and policy can help inform an integrated approach to appropriate care delivery in policy and practice according to the relevant priorities and circumstances.